Data Telling Stories and Stories Telling Data: The Role of Fiction in Shaping Ethnographic Truth - JT Torres (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The following essay explores the use of fiction in ethnographic research. While the concept of fiction as a research methodology is not a new one, most proponents claim that fiction is most useful in the writing of ethnographic data. Despite the gradual acceptance of arts-based methods in ethnography, there still remains a false dichotomy of art and scientific research. This essay contributes to the discussion by arguing that fiction also plays an active role in producing knowledge and truth. To make this argument, the author brings together in conversation scholars of art and literature with social researchers. While multiple examples are illustrated to show how fiction creates knowledge in ethnography, the primary focus will be Clifford Geertz’s (2005) “Notes on a Balinese Cockfight.” The purpose is to demonstrate how fiction can be a means of knowledge production, so long as it is situated in sound research methods.